2018
DOI: 10.1037/lhb0000299
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of army field manual interrogation approaches for educing information and building rapport.

Abstract: In 2016, the U.S. Congress mandated that federal intelligence interrogators adhere to the methods of the U.S. Army Field Manual FM 2-22.3 (AFM) and that the manual be revised based upon empirically based evaluations of the interrogation methods' effectiveness with interviewees motivated to withhold information. In the present study, 120 participants took part in a testing situation in which half were induced to cheat. All participants were then accused of cheating and interrogated with either (a) a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
14
1
Order By: Relevance
“…In addition to social influence principles and tactics, the topic of rapport has gained traction in research on forensic interviewing and for good reason: Rapport has been shown to be a central concept to all kinds of interactions pertaining to relationship building and formation, information elicitation, and therapeutic alliances for years (Alison, Alison, Noone, Elntib, & Christiansen, 2013; Christiansen, Alison, & Alison, 2018; Cialdini, 2009; Duke, Wood, Magee, & Escobar, 2018; Holmberg & Madsen, 2014; Oxburgh & Ost, 2011; Vallano & Compo, 2015). As a different component of social influence, studies have increasingly shown that rapport is important for successful interviews and investigations in forensic contexts as well (Abbe & Brandon, 2014; Alison et al, 2014; Holmberg & Madsen, 2014; Matsumoto & Hwang, 2018, 2019; Walsh & Bull, 2010).…”
Section: Social Influence: Liking Effects On Informational Elements Imentioning
confidence: 99%
“…In addition to social influence principles and tactics, the topic of rapport has gained traction in research on forensic interviewing and for good reason: Rapport has been shown to be a central concept to all kinds of interactions pertaining to relationship building and formation, information elicitation, and therapeutic alliances for years (Alison, Alison, Noone, Elntib, & Christiansen, 2013; Christiansen, Alison, & Alison, 2018; Cialdini, 2009; Duke, Wood, Magee, & Escobar, 2018; Holmberg & Madsen, 2014; Oxburgh & Ost, 2011; Vallano & Compo, 2015). As a different component of social influence, studies have increasingly shown that rapport is important for successful interviews and investigations in forensic contexts as well (Abbe & Brandon, 2014; Alison et al, 2014; Holmberg & Madsen, 2014; Matsumoto & Hwang, 2018, 2019; Walsh & Bull, 2010).…”
Section: Social Influence: Liking Effects On Informational Elements Imentioning
confidence: 99%
“…Behaviors were categorised as showing a personal interest if the interviewer was able to demonstrate that they were interested in the interviewee as an individual, by encouraging or engaging in topics of discussion that do not necessarily fall within the remit of the interview. to the true purpose of the interview to facilitate rapport-building (e.g., Duke et al, 2018b).…”
Section: Table 2 About Herementioning
confidence: 99%
“…For instance, the Scharffian knowledge illusion seems highly similar to the "we know all" approach advocated by the Army Field Manual (United States Army, 2006, 8-53 to 8-57) both in appearance and in labeling. Inconsistent with Scharff's technique, however, the Army Field Manual's "we know all" approach is compatible with approaches that involve accusatory pressure (see, e.g., Duke et al, 2018), and unlike Scharff's use of claims and avoidance of direct inquiry, the approach can entail "interjecting pertinent questions" when the source begins to provide new information. In contrast, the hypothesized underpinnings of the Scharffian illusion of knowing it all are similar to and consistent with the theoretical conceptualization behind the Strategic Use of Evidence (SUE) technique of interviewing and its extensions, which aim to influence interviewees' behavior in part by controlling their perception of how much the interviewer knows (see, e.g., Luke & Granhag, 2020).…”
Section: Scharff's Methods Of Interrogationmentioning
confidence: 99%